2019
DOI: 10.22603/ssrr.2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation Rates after Laminoplasty for Cervical Disorders: A 26-Year Period Survival Function Method Analysis

Abstract: Introduction Laminoplasty is a common surgery for cervical myelopathy. Previous studies have analyzed the reoperation rates in posterior decompression surgeries of the cervical spine. However, few studies have solely focused on midline-splitting laminoplasty (MSL) using a large number of patients. This aims to analyze the reoperation rates after MSL using the survival function method. Methods Between 1988 and 2013, 4,208 MSLs were performed as a primary operation for cervical myelopathy and enrolled in our spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…[35][36][37][38][39][40] For second surgery, 2 citations reported on the same dataset, therefore we considered 8 unique studies. [41][42][43][44][45][46][47][48][49] For adjacent level surgery, 2 sets of citations reported on the same dataset, therefore we considered 5 unique studies. [50][51][52][53][54][55][56] For Analysis #1 (second surgery), the included studies were published between 2009 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[35][36][37][38][39][40] For second surgery, 2 citations reported on the same dataset, therefore we considered 8 unique studies. [41][42][43][44][45][46][47][48][49] For adjacent level surgery, 2 sets of citations reported on the same dataset, therefore we considered 5 unique studies. [50][51][52][53][54][55][56] For Analysis #1 (second surgery), the included studies were published between 2009 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis #1 considered 2 randomized controlled trials, 41,42 3 large database studies, [43][44][45][46] and 2 single-center retrospective cohort studies. [47][48][49] At least 2 studies reported data for ACDF, ADR, LAMP, and PDIF. Overall, 49 950 patients underwent anterior cervical discectomy and fusion (ACDF), 357 underwent artificial disc replacement (ADR), 6800 laminoplasty, and 16 704 posterior laminectomy and instrumented fusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors referenced the installation of hydroxyapatite spacers as possibly related to higher infection rate. 10 Furthermore, considering the marked increase in healthcare costs, the cost of implants is becoming a major issue worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…
Main textCervical laminoplasty is the standard method for cervical myelopathy 1, 2 ; it has stable long-term results 3,4 . Although spontaneous interlaminar fusion following laminoplasty frequently occurs, it is rarely clinically problematic 5 .
…”
mentioning
confidence: 99%